Molecular evidence for the occurrence of the lichen genus Biatora (Lecanorales, Ascomycota) in the Southern Hemisphere - Rodriguez Flakus, Pamela; Printzen, Christian (Phytotaxa, 2014)
Based on anatomical investigations and a DNA barcoding approach the occurrence of a Biatora species from the B. rufidula group in Argentina and Chile is confirmed and the biogeographical implications briefly discussed. No morphological differences could be found that would distinguish the southern collections from typical B. rufidula. However, southern and northern samples appear paraphyletic within the B. rufidula clade. The South American material might therefore represent an undescribed species. Alternatively, the taxonomic status of the three northern species B. aegrefaciens, B. nobilis and B. rufidula might have to be reconsidered or the placement might be an artifact caused by the poor character sampling involved in the barcoding approach.